PENGARUH HARGA, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPATU MEREK YONGKI KOMALADI MENS: Studi Kasus Pada Matahari Mall Ciputra Cibubur - Nur Aditya Maulana, - (2019)
This research is a quantitative research that aims to determine the effect of Price, Product Quality and Promotion. The population in this study were consumers of the mall sun Ciputra Cububur who had bought mens shoes. The sample size was taken as many as 100 respondents, with non probability sampling method, especially incidental sampling. Data collection is done through the distribution of questionnaires. The analysis technique used is the method of PLS (Partial Least Square) analysis. The results of this study indicate that (1) Price has no significant effect on Purchasing Decisions. (2) Product Quality has no significant effect on Purchasing Decisions (3) Promotion has no significant effect on Purchasing Decisions.